When Yellow Isn’t Jaundice: Palmar and Plantar Discoloration in Carotenoderma – A Case Report - Aryal, Alisha; Poudel, Ramesh Sharma; Karmacharya, Himanshu; Shris, Nupendra (Journal of Nepalgunj Medical College, 2025)
Carotenoderma is characterized by a yellow-orange discoloration of the skin, typically resulting from the excessive consumption of carotene-rich fruits and vegetables. We report a case involving a patient who developed yellow pigmentation of the palms and soles in the absence of jaundice, secondary to a high intake of carrots, pumpkin, papaya, and green leafy vegetables. Although this condition is benign and does not require medical treatment, it is essential to distinguish it from pathological causes of yellow skin, such as jaundice.